KETERKAITAN PERILAKU PENGGUNA DENGAN POLA RUANG KAWASAN (STUDI KASUS: FASILITAS HIBURAN DI JL.KALIURANG DAN SETURAN-BABARSARI, YOGYAKARTA) - Fitria, Tika Ainunnisa (Jurnal Arsitektur dan Perencanaan (JUARA), 2018)
Abstract: The high growth of entertainment facilities currently trigger a disruption of environmental balance. The density of facilities in a space affects the frustration for the surrounding community. Space has important meaning for human. The socio-spatial approach is a paradigm in urban design. This research is a descriptive - qualitative through interviews method to absorb opinions, perceptions, and behavioral mapping. The goal is to find out the human behavior mapping, and identify the type and frequency of behavior and the linkages between the human behavior and the specific design features.Keywords: human behavior, spatial pattern, entertainment facilities